2001
DOI: 10.1128/aac.45.2.382-392.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytochrome P450 (CYP450) Isoforms by Isoniazid: Potent Inhibition of CYP2C19 and CYP3A

Abstract: Isoniazid (INH), introduced in the 1950s, continues to be one of the most safe and cost-effective agents used to treat tuberculosis (9). Because of the increasing incidence of tuberculosis that has resulted from the coepidemic of human immunodeficiency virus infection (32), the use of INH in the prevention (9, 17) and treatment (9) of tuberculosis is on the rise. INH is often given chronically to critically ill patients who are on multiple medications to treat tuberculosis and AIDS-related mycobacterial diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 49 publications
4
122
0
1
Order By: Relevance
“…It is considered to be caused by the inhibition of CYP (11 -14). In a recent publication, Desta et al have reported that INH was a potent inhibitor of CYP2C19 (competitive) and CYP3A (noncompetitive) in human liver microsomes (HLM) (13). Wen et al also showed the inhibition of CYP1A2, CYP2A6, CYP2C19, and CYP3A4 activities by INH, and they further suggested that these effects were increased by the preincubation of INH with HLM at 37°C for 15 min in the presence of NADPH (14).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is considered to be caused by the inhibition of CYP (11 -14). In a recent publication, Desta et al have reported that INH was a potent inhibitor of CYP2C19 (competitive) and CYP3A (noncompetitive) in human liver microsomes (HLM) (13). Wen et al also showed the inhibition of CYP1A2, CYP2A6, CYP2C19, and CYP3A4 activities by INH, and they further suggested that these effects were increased by the preincubation of INH with HLM at 37°C for 15 min in the presence of NADPH (14).…”
Section: Introductionmentioning
confidence: 97%
“…The report showed that the combination use of INH and PZA increased the adverse reaction induced by phenytoin, whose metabolism is mainly mediated by CYP2C9 (15 -17). Considering the minor inhibitory effect of INH on CYP2C9 activity as described by Desta et al (13), it was predicted that the observed inhibition might be caused by PZA. Furthermore, the inhibitory effect of PZA on CYPmediated metabolic activities has been also reported in rats (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, the available literature indicates that there are some similarities in the metabolism of isoniazid and certain SSRIs. 22,29,30,35 Although no substantial clinical evidence indicates that the combination of isoniazid and SSRIs is harmful, available evidence indicates that some SSRIs might be a better choice than others for concurrent treatment. Citalopram appears to be metabolized primarily by CYP2C19 and/or CYP3A4, both of which are inhibited by isoniazid, and thus it might not be the best choice for a patient taking isoniazid.…”
Section: Treatment Concerns For Patients With Comorbid Depression and Tbmentioning
confidence: 99%
“…While it has not been definitively established which isoenzymes are implicated in the metabolism of isoniazid, CYP2E1, CYP1A2, CYP2C9, CYP2C19, and CYP3A are inhibited to varying degrees by isoniazid (Table 4). 29,30 In a study employing human liver microsomes, Desta et al 30 indicated that CYP2C19 and CYP3A were inhibited potently by isoniazid in a concentration-dependent manner. Both enzymes were inhibited approximately 40% by doses in the therapeutic range.…”
Section: Treatment Concerns For Patients With Comorbid Depression and Tbmentioning
confidence: 99%
“…This inhibitory effect of isoniazid can increase the plasma concentrations of certain drugs to toxic levels. (3,36) The plasma concentrations of anticonvulsants, such as phenytoin and carbamazepine, can increase when these drugs are used in combination with isoniazid. (37) The same occurs with the benzodiazepines that are metabolized by oxidation (e.g., diazepam and triazolam), as well as with theophylline, valproic acid, disulfiram, acetaminophen, and oral anticoagulants.…”
Section: Other Drugsmentioning
confidence: 99%